Man’s Verses in the Holy Quran: An Objective Study - Hussein Ali, Rahim Mohammed (Journal of Tikrit University for Humanities, 2023)
According to the Holy Qur'an, it is said that humanity is regarded as a wonderful creation in the eyes of God. In accordance with the religious narrative, the deity fashioned Adam and imbued him with divine essence, designating him as the earthly representative and bestowing upon him a position of distinction. The intended aim and objective of sending messengers, selecting prophets, and sending down texts is to fulfill the role of man. The linguistic capacity of humans distinguishes them from jinn and other forms of repulsion. The attribution of Al-Ansi is ascribed to the human species. In terms of nomenclature, the human entity may be seen as a sentient and dynamic creature. The Qur'an employs many synonymous terms to refer to people, including "sons of Adam," "human beings," and "humans." It posits that the purpose of human creation is to serve God, and further elucidates that the human constitution includes inherent attributes such as vulnerability, obstinacy, and impatience. These inherent attributes have been seen in individuals from their inception, as ordained by a higher power. Additionally, there are additional qualities that individuals acquire during the course of their lifetime, such as unbelief, rejection of blessings, rivalry, disagreement, and despair.